Dispersion Topological Darkness at Multiple Wavelengths and Polarization States. Issue 12 (27th April 2017) - Song, Haomin; Zhang, Nan; Duan, Jiyuan; Liu, Zhejun; Gao, Jun; Singer, Matthew H.; Ji, Dengxin; Cheney, Alec R.; Zeng, Xie; Chen, Borui; Jiang, Suhua; Gan, Qiaoqiang
Abstract : Complete suppression of reflection is in principle achievable in ideal optical systems with unique optical features including complete light absorption, abrupt phase change, etc. However, conventional optical systems have an extremely tight tolerance on fabrication errors or inherent roughness of thin films or patterns. Therefore, it is difficult to realize the perfect reflectionless condition in practice. To overcome this challenge, a "topological darkness" concept with mild restrictions to the film quality is proposed using periodic metallic patterns and self‐assembled core–shell particles. Due to the topological effect, the robust nature of reflectionless surfaces is improved dramatically even in the presence of imperfections. Here the "mild" restriction will be further broken to realize reflectionless thin film systems using directly deposited thin films or random metal nanoparticles. Moreover, a broad absorption band is achieved by tuning the effective optical constants of the top absorbing layer. Remarkably, compared with conventional reflectionless phenomena under single polarization states and wavelengths, the system can realize multiwavelength zero‐reflection points for both polarization states on the same chip. These proof‐of‐concept results pave the way toward the development of practical applications using abrupt phase change and complete light absorption for label‐free optical sensing and enhanced light‐matter interaction within ultrathin film systems. Abstract : Reflectionless thin film systems, with a large tolerance on fabrication errors and surface roughness, are realized using directly deposited thin films or random metal nanoparticles. Moreover, a broad absorption band is achieved by tuning the effective optical constants of the top absorbing layer. Remarkably, the system can realize multiwavelength zero‐reflection points for both polarization states on the same chip.